New Mothers' Perceptions of Pressure to Breastfeed. Issue 3 (May 2022) - Korth, Christina X.; Keim, Sarah A.; Crerand, Canice E.; Jackson, Jamie L.
Abstract: Purpose: Develop a measure to quantitatively assess perceived pressure to breastfeed and examine associations between perceived pressure, emotional distress, and the breastfeeding experience and self-efficacy among women with 2- to 6-month-old infants. Study Design and Methods: A cross-sectional study using an online survey to assess perceived pressure to breastfeed, emotional distress, and the breastfeeding experience and self-efficacy was conducted. Participants were recruited through ResearchMatch, a national online service that matches potential participants to research studies, and online community forums (e.g., Facebook). Results: Women ( n = 187) reported themselves and society as the greatest sources of pressure. Pressure to breastfeed was negatively associated with the breastfeeding experience ( r = -.34, p < .01) and self-efficacy ( r = -.39, p < .01), but not emotional distress. Pressure to breastfeed remained a significant explanatory factor, even when considering demographic covariates, with the final models accounting for 16% and 20% of the variance in the breastfeeding experience and self-efficacy, respectively. Clinical Implications: Perceived pressure to breastfeed may be an important psychosocial factor to consider when aiming to improve women's breastfeeding experiences. Reducing perceived pressure may be beneficial for promoting breastfeeding outcomes. Abstract : This study reports on a measure to quantitatively assess perceived pressure to breastfeed and examines associations between perceived pressure, emotional distress, the breastfeeding experience, and self-efficacy among women with 2 to 6-month-old infants. Women reported themselves and society as the greatest sources of pressure. Pressure to breastfeed was negatively associated with the breastfeeding experience. Perceived pressure to breastfeed may be an important psychosocial factor to consider for improving women's breastfeeding experiences. Reducing perceived pressure may be beneficial for helping women meet their breastfeeding goals.